Use of weathered diesel oil as a low-cost raw material for biosurfactant production - Mariano, A. P. [UNESP]; Bonotto, Daniel Marcos [UNESP]; Angelis, D. F. [UNESP]; Pirôllo, M. P. S. [UNESP]; Contiero, Jonas [UNESP] (Brazilian Society of Chemical Engineering, 2008)
This work aimed to investigate the capability of biosurfactant production by Staphylococcus hominis, Kocuria palustris and Pseudomonas aeruginosa LBI, using weathered diesel oil from a long-standing spillage as raw material. The effect of the culture media (Robert or Bushnell-Haas) and of the carbon source (spilled diesel oil or commercial diesel oil) on biosurfactant production was evaluated. Erlenmeyer flasks (250 mL) containing the cell broth were agitated (240 rpm) for 144 h at 27±2ºC. Biosurfactant production was monitored according to the de Nöuy ring method using a Krüss K6 tensiometer. Considering the possibility of intracellular storage of biosurfactant in the cell wall of the cultures S. hominis and K. palustris, experiments were also done applying ultrasound as a way to rupture the cells. For the conditions studied, the cultures did not indicate production of biosurfactants. Results obtained with a hydrocarbon biodegradability test based on the redox indicator 2,6-dichlorophenol indophenol showed that only the commercial diesel was biodegraded by the cultures.
Keywords: Biosurfactant; Diesel oil; Raw material; Weathered